Study on Spontaneous Cerebrospinal Fluid (CSF) Rhinorrhoea: A Birmingham Experience (Medicine Today, 2013)
Spontaneous Cerebrospinal fluid (CSF) rhinorrhoea is not very common. The aim of this study is to identify the common features in the study group of patients with spontaneous CSF rhinorrhoea, to develop a hypothesis to explain the cause of this condition and to investigate the outcome of surgical techniques adopted to repair the leak. In this retrospective study we have reviewed all the cases of spontaneous CSF leaks attending and receiving treatment from the Department of ENT at Queen Elizabeth Hospital, Birmingham, from 1992 to 2002. Among the total number of 34 patients with CSF leaks, 15 were spontaneous in nature and formed our study group, of these 15 patients 14 were female; with age range from 37 to 70 years and a median age of 50 years. All the female patients were obese with a body mass index higher than normal range. We tried to identify common factors in the study group and it was evident that female sex, obesity and age play a key role in this condition. Follow up period ranged from 2 to 98 months and thirteen patients were asymptomatic but two patients remained symptomatic, one of these despite repeated surgical intervention. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14114 Medicine TODAY Vol.24(1) 2012 pp.40-43